1994
DOI: 10.1111/j.1365-263x.1994.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and severity of tooth wear and the relationship between erosion and dietary constituents in a group of children

Abstract: Summary. There is very little published information on the severity of tooth wear in children. The current investigation involved clinical examination of 101 children and an assessment of their dietary habits. Evidence of tooth wear was found in over 80% of maxillary incisor teeth, and 30% of primary molar teeth had some dentine exposed. There were 21 children who were regarded as having ‘mild’ erosion, 45 ‘moderate’ erosion and 35 ‘severe’ erosion. There were highly statistically significant differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
2
30

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(117 citation statements)
references
References 17 publications
8
77
2
30
Order By: Relevance
“…No entanto, bebidas com acidez elevada podem comprometer a saúde de consumidores se consumida com frequência, Millward et al (1994) constatou alta incidência de erosão dental em uma população com idade entre 4 e 16,5 anos e correlacionou este resultado ao alto consumo de sucos de frutas. Os valores médios encontrados para acidez total, expressa em g. As médias observadas dos sólidos solúveis (ºBrix) para o sabor maracujá atenderam o mínimo estabelecido pela legislação (BRASIL, 2003), no entanto para o sabor pêssego, as marcas A e B apresentaram os menores valores e abaixo do que estabelece os valores mínimos pela legislação vigente.…”
Section: Resultsunclassified
“…No entanto, bebidas com acidez elevada podem comprometer a saúde de consumidores se consumida com frequência, Millward et al (1994) constatou alta incidência de erosão dental em uma população com idade entre 4 e 16,5 anos e correlacionou este resultado ao alto consumo de sucos de frutas. Os valores médios encontrados para acidez total, expressa em g. As médias observadas dos sólidos solúveis (ºBrix) para o sabor maracujá atenderam o mínimo estabelecido pela legislação (BRASIL, 2003), no entanto para o sabor pêssego, as marcas A e B apresentaram os menores valores e abaixo do que estabelece os valores mínimos pela legislação vigente.…”
Section: Resultsunclassified
“…This is in contrast to a number of epidemiological studies which have shown significant relationships between acidic drink consumption and erosion [12,16,17]. Jervinen VK et al (1991) reported an apparent increase in the risk of erosion when sports drinks were consumed once or more per week, or when soft drinks were consumed daily [18].…”
Section: Type Of Sport Playedmentioning
confidence: 88%
“…Then within the unhealthy category if the food contained high sugar (i.e. more than 20% total sugars 33 ) or high sugar and low pH 13,14 (e.g. non diet fizzy drinks, acidic sweets) it was considered to be detrimental to oral health.…”
Section: Methodsmentioning
confidence: 99%